Les champignons parasites des racines de l'amandier - Guillaumin J.J. (Séminaire du GREMPA sur les portes-greffes de l'amandier, 1989)
The four main fungal diseases of the possible rootstocks for almond are reviewed, Phytophtora, Verticillium, Rossellinia and Armillaria, with their symptomathology and the literature information on the level of resistance or susceptibility of different rootstocks. Also presented are the results of two tests of resistance to Armillaria of several rootstocks, both engrafted and grafted with almond scions.
Séminaire du GREMPA sur les portes-greffes de l'amandier, 1988/11/29-30, Saragoza (Spain)